PROGRAM BIMBINGAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - ismaniar ismaniar ismaniar (Pedagogi: Jurnal Ilmu Pendidikan, 2017)
The present study is aimed at developing effective guidance program for increasing student’s learning motivation. The present study applies quantitative research approach with nonequivalent pre-posttest control group quasi-experimental design, and nonrandom-purposive sampling technique. The data were collected using inventory, interview, and documentary study. The study comes up with the main finding that the tested guidance program is proven to be effective for increasing learning motivation students of 11th grade at SMA Kartika XIX-2 Bandung.